1994
DOI: 10.1126/science.8023166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nigrostriatal Dopamine System on Acquired Neural Responses in the Striatum of Behaving Monkeys

Abstract: Dysfunction of the nigrostriatal dopamine system results in marked disorders of movement such as occur in Parkinson's disease. Functions of this dopamine-containing projection system were examined in monkeys trained in a classical conditioning task, and the effects of striatal dopamine depletion were tested. Unilateral dopamine loss substantially reduced the acquired sensory responsiveness of striatal neurons monitored electrophysiologically. This effect was ipsilateral and selective, and could be reversed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
309
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(337 citation statements)
references
References 26 publications
21
309
1
Order By: Relevance
“…There were also dynamic signal changes in the amygdala and the orbitomedial frontal cortex (OMFC), which are known to be involved in reward-based learning (35,36). Our results are thus consistent with models of basal ganglia function that propose that basal ganglia neurons integrate cortical signals with reward error signals carried by dopamine neurons during learning to build learned behaviors (26,27,37).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There were also dynamic signal changes in the amygdala and the orbitomedial frontal cortex (OMFC), which are known to be involved in reward-based learning (35,36). Our results are thus consistent with models of basal ganglia function that propose that basal ganglia neurons integrate cortical signals with reward error signals carried by dopamine neurons during learning to build learned behaviors (26,27,37).…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, recordings studies in the monkey's striatum showed that the associative and sensorimotor regions of the striatum contribute preferentially to the early and late stages of procedural learning, respectively (25). In rats, widely distributed changes in neuronal activity patterns have also been observed in the sensorimotor striatum during the course of learning (26,27), suggesting that the long-term representation of actions is built up through dynamic reorganization of neuronal activity in this territory. Finally, previous studies in humans have also reported activations within the associative striatum during the early stage of motor sequence learning (2,3,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the firing rate change of cholinergic interneurons is not closely related to the execution of tasks, but rather to the presentation of the conditioned, trigger stimulus (Aosaki et al, 1995). However, the firing is not simply sensory in nature because the cholinergic interneurons acquire their responses during conditioning, and their responses undergo extinction along with the conditioned movement (Aosaki et al, 1994a(Aosaki et al, , 1994b. Thus, the cholinergic pause develops with the behavioral conditioning, and becomes linked to the conditioned stimulus that predicts reward.…”
Section: Different In Vivo Responses Of Spiny and Cholinergic Neuronsmentioning
confidence: 99%
“…The pause responses of the cholinergic neurons to conditioned trigger stimuli in learned movement tasks is abolished when dopaminergic inputs to the striatum are removed or are blocked by DA antagonists (Aosaki et al, 1994a(Aosaki et al, , 1994bWatanabe and Kimura, 1998). In DA-denervated animals, the firing patterns of cholinergic neurons are severely altered such that the neurons fire synchronized rhythmic bursts (Raz et al, 1996).…”
Section: Neurophysiological Influences Over the Firing Of Cholinergicmentioning
confidence: 99%
“…DA depletion within the dorsal striatum, for example, reduces the responsiveness of striatal neurons to auditory, visual and tactile stimuli [6,98,101,122]. Prior to DA depletion, approximately 22% of neurons sampled from the dorsolateral caudate of the cat responded to tactile stimulation of the face; only 6% showed such tactile responses after MPTP-induced DA depletion [101].…”
Section: Da Activity Gates the Throughput Of Sensorimotor And Incentimentioning
confidence: 99%